Making Peace with the 60s - Burner, David, 1937- (Book collections on Project MUSE., 1998)
This history of America in the 1960s covers the civil rights movement, Kennedy and the Cold War, the counter-culture and Beat Generation, the student rebellion, and the Vietnam War. It argues that liberalism self-destructed by emphasizing race and ethnicity instead of class and wealth.